Comparative metabolomics of two nettle species unveils distinct high-altitude adaptation mechanisms on the Tibetan Plateau - Li-Juan Deng; Yin-Lei Li; Feng-Ying Wang; Xiang-Qian Sun; Richard I. Milne; Jie Liu; Zeng-Yuan Wu (BMC Plant Biology)
Abstract Background The extreme high-altitude conditions of the Tibetan Plateau, characterized by intense solar radiation, low temperatures, and reduced oxygen levels, poses significant challenges to plant survival. Plants inhabiting this region have evolved specialized mechanisms to adapt to high-altitude environments. While most studies have focused on genomic and ecological perspectives, few have explored adaptive mechanisms in a metabolic context. In particular, comparative studies examining similarities and differences in the metabolomes of closely related species are exceedingly rare. As sister species, the nettle species Urtica hyperborea and U. dioica are distributed above 4000 m above sea level, with a sympatric distribution on the Tibetan Plateau, they provide an ideal system to investigate the aforementioned question. Results In this study, we conducted non-targeted metabolic profiling of the leaves from U. hyperborea and U. dioica collected at three sympatric sites on the Tibetan Plateau. A total of 2906 annotated metabolites were detected. Differential metabolites at Sites 1 (4697 m) and 3 (4465 m) were enriched in pathways for flavonoid, flavone and flavonol, and phenylpropanoid biosynthesis. In contrast, Site 2, located at the highest altitude (5007 m), primarily exhibited enrichment in carbon metabolism pathways. Regarding the altitudinal variation of the same species, common metabolic pathways between the two groups included fructose and mannose metabolism, α-linolenic acid metabolism, and glycerophospholipid metabolism. The metabolic pathways enriched only inU. hyperboreaincluded starch and sucrose metabolism, galactose metabolism, and phenylpropanoid biosynthesis. The metabolically enriched pathways specific toU. dioicaincluded pantothenate and coenzyme A biosynthesis, as well as glutathione metabolism. Conclusions We found that the metabolic differences between the two sympatric species are primarily in carbohydrate and phenylpropanoid contents. The differential metabolites of the same species across different altitudes were enriched mainly in carbon metabolism pathways and lipid metabolism pathways. Thus, our study revealed that the high-altitude adaptation mechanisms of sympatric species are not identical. Moreover, adaptation strategies within the same species were generally consistent across altitudes, exhibiting only slight variations. This study provide novel insights into the adaptive metabolic strategies of U. hyperborea and U. dioica, contributing to a deeper understanding of the mechanisms underlying plant adaptation to extreme high-altitude conditions.